Finite Element Analysis of the Joint Surface of Concrete Filled Steel Tubular Frame Column and Precast Shear Wall. Issue 2 (May 2019) - Yang, Shaokun; Zheng, Lianqiong
Abstract: In order to study the connection performance of a new type of shear key to concrete filled steel tubular (CFST) frame column and precast shear wall, a numerical model is established by using the finite element software Abaqus, the mechanical properties of the combined shear wall are studied by the strength of post-poured concrete, the yield strength of the shear key steel and the spacing between the shearing bonds. The results show that the failure modes of specimens are mainly related to the strength of post-poured concrete and the yield strength of shear keys. When the specimens are damaged by shear bonds, the bearing capacity and ductility of the specimens increase obviously with the increase of the yield strength of the shear key steel and the shortening of the spacing between the shear keys. The change of strength of post-poured concrete has little effect on the working performance of specimens. When the specimens are damaged by post-poured concrete, the stiffness of the specimens is larger and the ductility is worse.